Organophotocatalytic selective deuterodehalogenation of aryl or alkyl chlorides - Li, Yanjun; Ye, Ziqi; Lin, Yu-Mei; Liu, Yan; Zhang, Yumeng; Gong, Lei (Nature communications, 2021)
Development of practical deuteration reactions is highly valuable for organic synthesis, analytic chemistry and pharmaceutic chemistry. Deuterodehalogenation of organic chlorides tends to be an attractive strategy but remains a challenging task. We here develop a photocatalytic system consisting of an aryl-amine photocatalyst and a disulfide co-catalyst in the presence of sodium formate as an electron and hydrogen donor. Accordingly, many aryl chlorides, alkyl chlorides, and other halides are converted to deuterated products at room temperature in air (>90 examples, up to 99% D-incorporation). The mechanistic studies reveal that the aryl amine serves as reducing photoredox catalyst to initiate cleavage of the C-Cl bond, at the same time as energy transfer catalyst to induce homolysis of the disulfide for consequent deuterium transfer process. This economic and environmentally-friendly method can be used for site-selective D-labeling of a number of bioactive molecules and direct H/D exchange of some drug molecules. Deuterodehalogenation of organic chlorides is a useful strategy to install deuterium atoms at specific positions, however, it has several drawbacks. In this study, the authors report an organophotocatalytic system consisting of an aryl-amine-based photocatalyst and a common disulfide co-catalyst, for efficient deuteration of a wide range of aryl chlorides, alkyl chlorides and other halides, at room temperature in air.